Multiwavelength hot-band excited triplet–triplet annihilation upconversion with Pt(ii)porphyrin complex/9, 10-bis(phenylethynyl)anthracene and multiple encryption information applications. Issue 6 (31st January 2023) - Chen, Quanlun; Ye, Changqing; Wan, Shigang; Chen, Shuoran; Liang, Zuoqin; Li, Lin; Shi, Yizhong; Wang, Xiaomei
Abstract : Multiwavelength hot-band excited low-powered upconversion was accomplished with the excitation of a sensitizer at hot-band vibrational energy levels in the ground state, and provides a new way of transcending traditional absorption law restriction. Abstract : Multiwavelength hot-band excited triplet–triplet annihilation upconversion (TTA-UC) was accomplished with the excitation of a sensitizer at hot-band vibrational energy levels in the ground state. Selective excitation of Pt(ii )tetraphenyltetrabenzoporphyrin (PtTPBP ) at 635 nm, 655 nm, 671 nm or even 785 nm (IR) all can induce the emissions of 9, 10-bis(phenylethynyl)anthracene (BPEA ) with the maximum anti-Stokes shift at 0.86 eV, which significantly increases anti-Stokes shifts and shows potential application in information multiple encryptions.